Implementación del sistema de contabilidad comercial a la estación de servicios “Amazonas” de la ciudad de Yantzaza, periodo enero a marzo del 2013 - Armijos Cabrera, Zuly Arelis (2015)
This work is titled "IMPLEMENTATION OF SYSTEM FROM ACCOUNTING COMMERCIAL TO STATION FROM SERVICES “AMAZON” OF THE CITY YANTZAZA, PERIOD JANUARY TO MARCH 2013", and was raised in order to present practical implementation of a proper accounting system for a gas station or service station. This research addresses an issue of great importance to trade and economic development of companies such as service stations; it is framed in the application of commercial as a tool for assessing the Results of an accounting period led to increased economic efficiency and business decisions overlooking increase efficiency and effective use of resources. His process presents in detail the implementation of the objectives of the business accounts, containing the same since the initial inventory, the Plan and Accounting Manual, used to correct the record of the accounting process, with the Purchase Daily Journal Sales, Transportation Registers, Deposit, purchases of materials, payroll, all records of original entry, etc. Older., which was recorded in every transaction of a quarter, observing Standards Accounting, Taxation Law and Internal Revenue, culminating in the preparation and presentation of financial to a service station whose results contributes and facilitates decision-making by his owner. We concluded that the Amazon Service Station does not have proper accounting and therefore are not aware of each sales and purchasing real account, so we recommend the implementation of an accounting system as soon as possible in this station